Gross pathology monitoring of cattle at slaughter - Rezac, Darrel James (Kansas State University, 2013)
A series of studies were conducted in order to develop, test, implement, and utilize an objective and comprehensive gross pathology scoring system for cattle at slaughter. Individual lung, liver, and rumen gross pathology data was collected from 19,229 head of cattle and corresponding individual pre-harvest and carcass data for a subset of 13,226 head.. Across the entire population 22.6% and 9.8% of cattle displayed mild and severe lesions, respectively. Severe lung lesions at the time of slaughter were associated with a decreased ADG of 0.07 kg/ day and a carcass weight 7.1 kg less than that of their cohorts with no visible signs of pulmonary BRDC lesions (P < 0.01). Overall, 68.6 % of cattle observed had normal livers, free from abscesses and other abnormalities. Cattle with a severe liver abscess at the time of slaughter were associated with a 0.10 kg/day during the feeding period (P < 0.01). Of cattle severely affected by liver abscesses (A+, 4.6%), 14.9% also displayed severe BRDC lung lesions and 28.3 % of cattle displayed mild BRDC lung lesions. Rumenitis lesions were observed in 24.1% of the overall study population. Severe rumenitis lesions were associated with a significant decrease in average daily gain and carcass weight (0.03kg/day and 2.20 kg, respectively, P < 0.01). The system was also implemented on a population of cull cows at a commercial abattoir in the Great Lakes region of the U.S. (n=1,461; 87% Holstein, 13% other cows). Severe liver abscesses, were observed in 18.5% of cull cows at slaughter. Severe rumenitis lesions or rumenitis scars were observed in 10% and severe BRDC lesions were observed in 10.3% o of the population. A prospective study of a commercially available, direct fed microbial oral drench of Megasphaera elsdenii (NCIMB 41125) was conducted in 4,863 head of yearling feeder cattle. No significant effects of treatment were detected for final live weight (599 vs. 601 kg; P=0.79) or hot carcass weight (386 vs. 387 kg P=0.81) for Con and M.e., respectively. Fourteen point two percent and 14.0% of Con and M.e., respectively displayed a liver abscess of varying severity at the time of slaughter. Overall, 8.27 and 7.96% % of Con and M.e. cattle were observed with an altered rumen epithelial health status. The ordinal odds ratio of a M.e. treated animal having a more severe liver abscess score or rumen health score was not significant (Estimate: 0.96, 95% C.L. 0.733-1.259, P=0.771; Estimate: 1.01, 95% C.L. 0.625-1.63 P=0.96, respectively.) Comprehensive monitoring of gross pathology at slaughter is commercially plausible and provides valuable data for veterinarians, nutritionists and management personnel.
Keywords: Beef cattle; Dairy cattle; Bovine respiratory disease; Ruminal acidosis; Rumenitis-liver abscess complex; Carcass bruising; Animal Diseases (0476); Animal Sciences (0475); Veterinary Medicine (0778)